Genetical, Cytological & Biological Studies of OWSWF, Chrysomyabezziana (Vill.) (Diptera: Calliphoridae) Exposed to GammaRadiation: VII. Effect on Dispersal & Flight Ability Index - الطويل أياد; السراي ميسون; محمود عماد (Iraqi Journal of Science, 2025)
This study showed that the flight ability index of the irradiated adult ofOWSWF, Chrysomya bezziana as 5 days old pupae with the doses ranged 15-90 Gywas not significantly different from that of the control group during an experimentcarried out under laboratory conditions. But when the experiment was carried outunder field conditions, there was considerable decreases in the flight ability &dispersal of the irradiated flies which irradiated as 5 days old pupae with thefollowing doses of gamma rays 45 & 75 Gy then released at the temperature of (18-20)C, while an increases in the flight ability & dispersal were noticed if the fliesreleased at the temperature of (31-34)C & the flies irradiated with 60 & 90 Gy ofgamma rays as 5 days old pupae. These results indicated the importance of choosingthe correct time for releasing sterile insect if an programm for eradicating this pestwill be used in near future.